Perceptions of event notification following discharge to improve geriatric care: qualitative interviews of care team members from a 2-site cluster randomized trial. (10th May 2021) - Franzosa, Emily; Traylor, Morgan; Judon, Kimberly M; Guerrero Aquino, Vivian; Schwartzkopf, Ashley L; Boockvar, Kenneth S; Dixon, Brian E
Abstract: Objective: To assess primary care teams' perceptions of a health information exchange (HIE) event notification intervention for geriatric patients in 2 Veterans Health Administration (VHA) medical centers. Materials and Methods: We conducted a qualitative evaluation of an event notification alerting primary care teams to non-VHA hospital admissions and emergency department visits. Data were collected through semistructured interviews (n = 23) of primary care team physicians, nurses and medical assistants. Study design and analysis were guided by the Consolidated Framework for Implementation Research (CFIR). Results: Team members found the alerts necessary, helpful for filling information gaps, and effective in supporting timely follow-up care, although some expressed concern over scheduling capacity and distinguishing alerts from other VHA notices. Participants also suggested improvements including additional data on patients' diagnosis and discharge instructions, timing alerts to patients' discharge (including clear next steps), including additional team members to ensure alerts were acted upon, and implementing a single sign-on. Discussion: Primary care team members perceived timely event notification of non-VHA emergency department visits and hospital admissions as potentially improving post-discharge follow-up and patient outcomes. However, they were sometimes unsure of next steps and suggested the alerts and platform could be streamlined for easier use. Conclusions: Event notifications may be a valuable tool in coordinating care for high-risk older patients. Future intervention research should explore the optimal amount and types of information and delivery method across sites and test the integration of alerts into broader care coordination efforts.